PREVALENCE OF REFRACTIVE ERROR AMONG MEDICAL STUDENTS: IMPLICATIONS FOR IRREGULAR EYE SCREENING SERVICES IN NIGERIA - L, IBRAHIM; O. A, KINGSLEY; HUSSAINY YUSUF, ANAS (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Refractive error is caused by an error in the refractive power of the eye due to alteration in the ocular length. Uncorrected Refractive error is the second leading cause of visual impairment worldwide. Uncorrected refractive errors are common visual impairment among medical students. The study was designed to determine the prevalence of Refractive error among medical students. A cross-sectional study conducted from October, 2021 – March, 2021 among Medical students. 157 students were selected by simple sampling technique, aged between 17 to 25 years. Demographic data of each student was obtained by a combination of self-administered interviewer questionnaire and clinical eye examination. The history of the past and previous eye checkup and use of glasses were also determined. Snellen chart, pinhole, pen-torch, ophthalmoscope, retinoscope were used to determine refractive error among the students. The study showed that 14.0% of `the students had visual impairment, and the prevalence of refractive error was found to be 10.8% with a preponderance of myopia at 70.6%, hyperopia at 17.6%, then astigmatism at 11.8%. Out of the students with myopia, 88.2% had low degree myopia. The study shows that 18.2% of the students were not using corrective lenses. Refractive error is a significant cause of visual impairment and regular eye screening is necessary for early detection and correction of refractive errors among medical students.